Mutual radicalization : how groups and nations drive each other to extremes - Moghaddam, Fathali M. (American Psychological Association, 2018)
"This book is about the powerful dynamic and destructive process termed mutual radicalization, which occurs when two groups take increasingly extreme positions opposing one another. It discusses the psychological processes underlying some key cases of mutual radicalization. The book develops a road map of how mutual radicalization takes place, shaped by underlying psychological processes. Each case study is presented within the same three-stage framework of mutual radicalization: group mobilization, extreme ingroup cohesion, and antagonistic identity transformation. The book is organized in four parts comprising twelve chapters. Part I consists of two case studies involving a nation-state and a nonstate actor, Israel--Palestine; a case involving two nation-states, Iran--United States; and two case studies involving Islamist terrorism and nation-states (the United States and the European Union). Part II describes case studies of nations in transition and in danger of moving further along the path of mutual radicalization. They represent a range of the most important 21st-century conflicts: China--Japan, North Korea--South Korea, and Pakistan--India. Part III presents three case studies of within-state or "domestic" mutual radicalization. The first involves mutual radicalization leading to gridlock in U.S. politics during the last six years of the Obama presidency, the second focuses on mutual radicalization in U.S. politics as represented by the Trump and Sanders presidential election campaigns, and the third explores the relationship between the National Rifle Association and gun-regulation groups in America. Part IV examines solutions to mutual radicalization, with proposals for how to break the cycles of distrust and violence."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)